2018
DOI: 10.3389/fpsyg.2018.01003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blindness on Long-Term Episodic Memory for Odors and Sounds

Abstract: We recently showed that compared with sighted, early blind individuals have better episodic memory for environmental sounds, but not odors, after a short retention interval (∼ 8 – 9 min). Few studies have investigated potential effects of blindness on memory across long time frames, such as months or years. Consequently, it was unclear whether compensatory effects may vary as a function of retention interval. In this study, we followed-up participants (N = 57 out of 60) approximately 1 year after the initial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The lower recognition score for odours than for other sensory cues confirmed our hypothesis. It is also in agreement with studies where the recognition of odours was compared to the recognition of other stimuli, such as faces (Cornell Kärnekull et al, 2015), environmental sounds (Cornell Karnekull et al, 2018) and common pictures (Cameron et al, 2021), even if no recognition memory performance differences were observed between odours and abstract simple shapes (Lawless, 1978). This reduced ability to recognize unidentifiable odours can be attributed to the difficulty of verbally categorising and communicating about odours (Jraissati & Deroy, 2021;Majid & Burenhult, 2014).…”
Section: Music and Faces Outperform Odours For Recognition Memorysupporting
confidence: 88%
“…The lower recognition score for odours than for other sensory cues confirmed our hypothesis. It is also in agreement with studies where the recognition of odours was compared to the recognition of other stimuli, such as faces (Cornell Kärnekull et al, 2015), environmental sounds (Cornell Karnekull et al, 2018) and common pictures (Cameron et al, 2021), even if no recognition memory performance differences were observed between odours and abstract simple shapes (Lawless, 1978). This reduced ability to recognize unidentifiable odours can be attributed to the difficulty of verbally categorising and communicating about odours (Jraissati & Deroy, 2021;Majid & Burenhult, 2014).…”
Section: Music and Faces Outperform Odours For Recognition Memorysupporting
confidence: 88%
“…However, it should be noted that all previous studies on multisensory illusions in congenitally blind individuals have focused on perceptual tasks in the auditory and tactile senses, where increases in perceptual abilities have been demonstrated (Hötting & Röder, 2004, 2009). In contrast, the majority of olfactory studies demonstrate that olfactory abilities are similar for blind and sighted (Cornell Kärnekull et al., 2016, 2018, 2020; Sorokowska et al., 2019). Thus, based on this fact and earlier multisensory illusions, blind individuals should be as susceptible to multisensory odor illusions as sighted.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the majority of evidence suggests that congenitally or early blind individuals are generally less affected by multisensory illusions. However, in contrast to audition and touch, the majority of studies in olfaction show small or, in most of the cases, no differences in olfactory abilities between sighted and blind people (e.g., odor threshold, discrimination, identification, and memory), with the only difference being in odor imagery where blind individuals outperform sighted (Cornell Kärnekull et al., 2016, 2018, 2020; Sorokowska et al., 2019). This suggests that blind individuals would not be able to draw on enhanced odors skills to separate verbal information from the odor percept per se.…”
Section: Introductionmentioning
confidence: 99%